English Taboo Language in “Wade” Movie - Silalahi, lamsahat; Ambalegin, Ambalegin (eScience Humanity Journal, 2023)
The goal of this qualitative research was to identify the types and function of taboo language used by the characters in the "Wade" movie. This research applied the theories of Battistella (2005) to identify the types of taboo language. The data were taken from all of the characters' taboo language-expressing utterances. This study used the observational method and non- participatory technique by using Sudaryanto's (2015) theory to gather data. This research used identity method data and referential competence in equalizing technique (Sudaryanto, 2015). The findings of this study were presented as follows. First, the characters in the Wade movie use four different sorts of taboo language. They were obscenity, vulgarity, profanity, and epithet. Obscenity, epithets, vulgarity, and profanity were the most often utilized taboos, accounting for 12 of the 30 data points from the Wade movie. Second, the movie Wade had 30 instances of four prohibited language functions. Profanity appeared as the latest. The reason for the seven instances of scorn, the twelve instances of self-promotion, the six instances of provocativeness, and the two instances of mocking authority was that the major theme of the film is a romantic comedy, which was not criticized much to the institution such as government and organization in society.